The experiences of women workers in mining: a case study of Hwange Colliery Company Limited. - Nhawu, Ndi Ngonidzashe (Midlands State University, 2017)
The purpose of the study was to explore the positive and negative experiences of women in mining at HCCL. The objectives of the study included investigating women miners’ access to mobility and power structures, fairness in task assignment, exploring women miners’ insights on the handling of disciplinary and performance issues, the execution of the gender mainstreaming role by HR and the challenges women face from stereotypical behavior and exclusion. Some of the positive experiences included women being able to compete equally with men in task execution because of technology and enactment of policies such as the equal opportunity policy that have helped women attain a certain degree of mobility and power structures within the mining hierarchy. The research also discovered male hostility may be rife in mining but there is a new breed of men who are accommodative and appreciative of women miners. Gradual changes are taking form for women in mining but they still have a long way to go before equality is achieved. Their rarity and scarcity leaves them vulnerable to unwanted sexual attention and male hostility through sexist language and exclusion. The research was based on an exploratory qualitative research design. To gather data the researcher used questionnaires and interviews. A combined thirty-six (36) participants responded to the questionnaires and interviews. The research was qualitative and the researcher used the thematic approach for data analysis. The major finding from the research was that the absence of women in executive positions negatively affects the power balances between women and male miners. This is because gender relations are related to power relations thus men in top management positions will pursue strategies that are influenced by their gender. The researcher noticed that women do not have difficulty in raising into junior management positions yet they experience the glass ceiling effect when it comes to attaining top management positions. The researcher recommended that intensive implementation and management of the STEM initiative so as to increase representation of women in mining by increasing their enrolment in science and technology related fields.